VISUAL CONNECTIVITY AND STREET NODES LIVEABILITY: A CASE STUDY OF JOHOR BAHRU HERITAGE DISTRICT, MALAYSIA - Amirul Hakim Jamil; Sharifah Salwa Syed Mahdzar, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
In Malaysia, streets could be identified as public spaces for various activities especially at the heritage district. This study aims to promote street node as a potential liveable and sociable public space between buildings focussing on Johor Bahru city. The paper objectively proposes a method on identifying street nodes liveability pattern and introduce a relationship between occupied socio-physical and visual connectivity. It is argued that people sitting and standing at the sidewalks can also be affected by the visual connection amongst the pedestrians in addition to the condition to the street itself. The distribution of static activities of people are measured according to socio-physical elements and visual graph analysis (VGA) in Depthmap software. The results show simple relationship between the socio-physical element and the presence of static activities of people in the walkway. It is suggested that street designers, business operator and the authority could be able to create liveable spaces according to the environmental conditions and types of existing static activity.